Prenatal fine particulate matter exposure, placental DNA methylation changes, and fetal growth. (February 2021) - Zhao, Yingya; Wang, Pengpeng; Zhou, Yuhan; Xia, Bin; Zhu, Qingyang; Ge, Wenzhen; Li, Jialin; Shi, Huijing; Xiao, Xirong; Zhang, Yunhui
Highlights: Prenatal PM2.5 exposure was associated with reduced fetal growth. Prenatal PM2.5 exposure could lead to aberrant changes in DNA methylation profile of placenta genome. Methylation in BID (BH3 interacting domain death agonist) partially mediated the effects of PM2.5 exposure on fetal growth. Prenatal PM2.5 exposure might disrupt fetal growth by affecting placental DNA methylation. Abstract: This study was designed to examine the impact of prenatal fine particulate matter (PM2.5 ) exposure on fetal growth and the underlying placental epigenetic mechanism in a cohort of Chinese women. Within the prospective Shanghai Mother-Child Pairs cohort (Shanghai MCPC), 329 women carrying singleton pregnancy with a due date in 2018 were recruited between 2017 and 2018. Maternal PM2.5 exposure levels were estimated using gestational exposure prediction model combining satellite-driven ambient concentrations and personal air sampling. Fetal growth characteristics were evaluated by prenatal ultrasound examinations and anthropometric measurements at birth. In a discovery phase, whole-genome DNA methylation analysis was performed using the Infinium 850 K array. In a validation phase, placental DNA methylation was measured using bisulfite pyrosequencing for five candidate genes that showed the most significant alterations and function relevance in our methylation array screen, including BID (BH3 interacting domain death agonist), FOXN3 (Forkhead box N3), FOXP1 (Forkhead box P1), IGF2 (Insulin-like growth factor 2) and HSD11B2 (Hydroxysteroid 11-beta dehydrogenase 2). Multivariate linear regression models were applied to examine the associations among PM2.5 exposure, fetal growth characteristics and DNA methylation on placental candidate genes. Sobel tests were used to evaluate the mediating role of DNA methylation in multivariable models. After excluding women who withdrew or failed to provide placenta, a total of 287 pregnant women with an average age of 30 entered the final analysis. Increased PM2.5 exposure was significantly associated with reduced biparietal diameter (BPD) (β: −0.136 mm, 95% CI: −0.228 to −0.043), head circumference (HC) (β: −0.462 mm, 95% CI: −0.782 to −0.142), femur length (FL) (β: −0.113 mm, 95% CI: −0.185 to −0.041) and abdominal circumference (AC) (β: −0.371 mm, 95% CI: −0.672 to −0.071) in the second trimester and birth length (β: −0.013 cm, 95% CI: −0.025 to −0.001). Prenatal PM2.5 exposure could lead to aberrant changes in DNA methylation profile of placenta genome, which were mainly enriched in reproductive development, energy metabolism and immune response. DNA methylation of IGF2 and BID showed significant associations with PM2.5 exposures during all exposure windows. In addition, BID methylation was negatively correlated with HC (β: −1.396 mm, 95% CI: −2.582 to −0.209) and BPD (β: −0.330 mm, 95% CI: −0.635 to −0.026) in the second trimester. Further mediation analysis indicated that BID methylation mediated about 30% of the effects of PM2.5 exposure on HC. These findings collectively suggested that prenatal PM2.5 exposure may cause adverse effects on fetal growth by modifying placental DNA methylation.